The first report of atovaquone/proguanil-induced vanishing bile duct syndrome: Case report and mini-review. Issue 32 (November 2019) - Abugroun, Ashraf; Colina Garcia, Ibett; Ahmed, Fatima; Potts, Steven; Flicker, Michael
Abstract: The combination of Atovaquone and Proguanil (Malarone™) has been widely used for treatment and prevention of Plasmodium falciparum malaria. Transient elevation of liver enzymes is a recognized side effect of the medication. The association of Vanishing bile duct syndrome (VBDS) with the use of Atovaqoune/Proguanil was not previously reported. We describe a case of a 62-year-old male with no history of liver disease who presented with painless jaundice after receiving malaria prophylaxis with Atovaquone-proguanil for 25 days. The patient developed severe hepatitis with Vanishing bile duct syndrome. This case highlights a serious side effect of a usually well-tolerated medication.